Two novel pathogenic PDX1 variants in two Japanese patients with maturity-onset diabetes of the young - Tanaka, Satoshi; Akagawa, Hiroyuki; Hase, Michiyo; Iwasaki, Naoko (Human genome variation, 2025)
Maturity-onset diabetes of the young type 4 (MODY4, PDX1-MODY) is a monogenic diabetes caused by the PDX1 gene. Here we detected two novel heterozygous missense variants, NM_000209.4(NP_000200.1):c.443G>T, p.(Arg148Leu) and c.442C>G p.(Arg148Gly), in two Japanese patients. Pathogenicity testing revealed a loss of function in both variants. Family members had severe diabetic complications, including proliferative retinopathy and overt nephropathy such as end-stage renal disease. Laboratory testing indicated persistently high glucose levels, at least partially caused by reduced postprandial insulin secretion.